Impact of negative symptoms on health-related quality of life in schizophrenia - Li, Yanhui; Rekhi, Gurpreet; Ang, Mei San; Lee, Jimmy (Frontiers in Psychiatry, 2023)
Evidence regarding the association of Negative Symptoms (NS) dimensions with Health-related Quality of Life (HRQoL) is limited and no prior study has looked into contributions of NS domains on HRQoL. This study bridges the gap by examining the associations of NS, its two dimensions (Motivation and Pleasure, and Emotional Expressivity) and five domains (Anhedonia, Avolition, Asociality, Blunted affect and Alogia) with HRQoL in schizophrenia. 274 individuals with schizophrenia were assessed on the Positive and Negative Syndrome Scale (PANSS) and Brief Negative Symptom Scale (BNSS). PANSS scores were mapped to EuroQol five-dimensional (EQ-5D-5L) utility scores using an algorithm previously validated in Singapore, and the resulting EQ-5D-5L scores were used as a measure of HRQoL. Multiple linear regression analyses of the two NS dimensions and five NS domains against EQ-5D-5L showed that a lower severity of NS, specifically that of the Motivation and Pleasure (MAP) dimension and asociality domain was associated with higher HRQoL. Our findings highlight the importance of targeting NS, particularly MAP and asociality, in improving HRQoL in schizophrenia.